Go to the forest! Exploring the orderings of Swedish Nature-Based Integration. (December 2021) - Singleton, Benedict E.
'Nature-Based Integration' (NBI) has been proposed as a solution to two prominent issues in contemporary Nordic societies: increasing separation from nature among 'modern' societies; and the need to 'integrate' groups of diverse newcomers. This article examines NBI activities in Örebro County, central Sweden, exploring how these practices seek to bring immigrants into a shared Swedish experiential landscape that forms part of the work of ordering Sweden as a community. These activities form part of an ordering project, within which 'Swedes' and 'newcomers' are situated, drawing on extant nationalist orderings. Likewise, it represents part of an effort to enact a sustainable Sweden in an international world. Drawing on research on environmental racism and (in)justice, this article homes in on the norms implicit and explicit to this ordering. It then discusses the implications of this, highlighting (arguably unavoidable) coercive elements. Furthermore, the long history of outdoor lifestyle as a pillar of Swedish nationalism and the embracing of such activities by the Swedish far right highlight that nature may also become a site of conflict as much as conciliation. Finally, the article considers the types of environmental action arising from the NBI orderings and the likelihood of meaningful environmental change.